Pitch Characteristics Before Ulnar Collateral Ligament Reconstruction in Major League Pitchers Compared With Age-Matched Controls. Issue 6 (14th June 2016) - Prodromo, John; Patel, Nimit; Kumar, Neil; Denehy, Kevin; Tabb, Loni Philip; Tom, James
Background: Ulnar collateral ligament reconstruction (UCLR) is commonly performed in Major League Baseball (MLB) pitchers, but little is known about the preoperative pitch type and velocity characteristics of pitchers who go on to undergo UCLR. Hypothesis: Pitchers who required UCLR have thrown a greater percentage of fastballs and have greater pitch velocities compared with age-matched controls in the season before injury. Study Design: Case-control study; Level of evidence, 3. Methods: MLB pitchers active during the 2002 to 2015 seasons were included. The UCLR group consisted of MLB pitchers who received UCLR between 2003 and 2015, utilizing the season before surgery (2002-2014) for analysis. The control group comprised age-matched controls of the same season. Players who pitched less than 20 innings in the season before surgery were excluded. Pitch types were recorded as percentage of total pitches thrown. Pitch velocities were recorded for each pitch type. Pitch type and pitch velocities during preoperative seasons for UCLR pitchers were compared with age-matched controls using univariate and multivariate models. Results: A total of 114 cases that went on to UCLR and 3780 controls were included in the study. Pitchers who went on to UCLR appear to have greater fastball, slider, curveball, changeup, and split-fingered fastball velocities; there were no significant differences in pitch selection between the 2 groups. Conclusion: In the season before surgery, MLB pitchers who underwent UCLR demonstrated greater fastball, slider, curveball, changeup, and split-fingered fastball velocities, with no significant difference in pitch type.